Modeling Carbon-Nanotube-Based Nano-Electro-Mechanical Systems for Application in Mass Detection Sensors: Online First: 29/05/2026 - Dai D. Mai,; Tuan D. Vu,; Si T. Do, (Journal of Technical Education Science, 2026)
Carbon nanotube-based nano-electro-mechanical systems (NEMS) have emerged as highly promising platforms for ultrasensitive mass detection and nanoscale signal processing. This paper presents a comprehensive investigation of the resonance behavior, tunability, and instability thresholds of such devices under electrostatic actuation and mass loading. A coupled electro-mechanical finite-element model is developed, wherein the nanotube is represented by shell elements, electrostatic actuation is modeled via reduced-order transducer elements, and adsorbed particles are introduced through lumped mass elements. The proposed model is rigorously validated against beam-theory results and published molecular-dynamics data, yielding mean errors of 1.02%-2.39%. Parametric studies demonstrate strong voltage tuning; for a baseline device, the fundamental frequency rises significantly from 549.28 MHz (0 V) to 2108.1 MHz (60 V). Furthermore, the analysis reveals a geometry-dependent pull-in limit and confirms that mass adsorption causes a commensurate reduction in resonant frequency. Geometrically nonlinear analysis also predicts a higher instability threshold compared to linear models. Ultimately, these findings validate a compact and effective design framework for optimizing CNT geometry and bias conditions in tunable NEMS mass sensors.